2019
DOI: 10.1002/jsfa.9825
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of phenolic profiles and antioxidant capacities of common buckwheat and tartary buckwheat produced in China upon thermal processing

Abstract: BACKGROUND: Buckwheat products are receiving increasing attention because of their high nutritive values and significant health-promoting properties. In the present study, 15 buckwheat products grown in different parts of China were investigated. Representative common or tartary buckwheat samples were further subjected to soaking, roasting, microwave cooking, boiling and steaming treatments. Colorimetric analyses and high-performance liquid chromatography (HPLC) analyses were performed to determine the phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 44 publications
2
31
2
Order By: Relevance
“…Kalinová et al (2019) [13] reported the phenolic content in different parts of common buckwheat, in which the content of catechin, epicatechin, and rutin (20.87, 56.51 and 52.48 mg kg −1 d.w.) in groat was in the same order of magnitude as that obtained for whole buckwheat flour in our work [13]. Liu et al (2019) [27] reported the phenolic profiles and antioxidant capacities of common buckwheat and Tartary buckwheat, in which the content of rutin in common buckwheat was 62.19 mg kg −1 d.w. and this value was similar to that obtained in whole buckwheat in the present study (87.33 mg kg −1 d.w.) [27]. Hence, our results are in accordance with the previous studies.…”
Section: Quantification Of Phenolic Compounds In Buckwheat Fractionssupporting
confidence: 84%
“…Kalinová et al (2019) [13] reported the phenolic content in different parts of common buckwheat, in which the content of catechin, epicatechin, and rutin (20.87, 56.51 and 52.48 mg kg −1 d.w.) in groat was in the same order of magnitude as that obtained for whole buckwheat flour in our work [13]. Liu et al (2019) [27] reported the phenolic profiles and antioxidant capacities of common buckwheat and Tartary buckwheat, in which the content of rutin in common buckwheat was 62.19 mg kg −1 d.w. and this value was similar to that obtained in whole buckwheat in the present study (87.33 mg kg −1 d.w.) [27]. Hence, our results are in accordance with the previous studies.…”
Section: Quantification Of Phenolic Compounds In Buckwheat Fractionssupporting
confidence: 84%
“…Owing to the genotypes and growth-influencing environmental factors of buckwheat varieties, significant differences were seen in TPC/TFC. Many studies have confirmed that phytochemical compositions of cereal crops mainly depend qualitatively and quantitatively on its genotypes and environmental factors that influence growth [30,31]. Different lowercase letters (a-e) mean statistically significant differences following different samples at the same fractions (p < 0.05).…”
Section: Total Phenolic Contents (Tpc) and Total Flavonoid Contents (mentioning
confidence: 97%
“…Qin et al (2010) reported that the FP contents (25.3 mg GAE/g DW) were higher than the BP contents (1.8 mg GAE/g DW) in tartary buckwheat bran [15]. Liu et al (2019) confirmed that the highest phenolic content of 15 buckwheat varieties from China was only 7.32 mg GAE/g DW, which was lower than that of samples from Shanxi (13.74 mg GAE/g DW) [30]. In this work, we found that the average TPC and TFC of tartary buckwheat samples (TPC: 9.97 mg GAE/g DW; TFC: 19.26 mg RE/g DW) were significantly higher than those of the common buckwheat samples (TPC: 6.47 mg GAE/g DW; TFC: 10.87 mg RE/g DW) (p < 0.001).…”
Section: Total Phenolic Contents (Tpc) and Total Flavonoid Contents (mentioning
confidence: 99%
“…These values were lower than those obtained in bran meal, light flour, and de-hulled grain meal, and also, the content of rutin in seed coat (54.23 mg/kg d.w.) represents a quart of the phenolic bran meal (214.99 mg/kg d.w.) obtained in our study. This could be due to the different cultivar and/or the different methodology of determination of phenolic compounds (by MS detection a higher number of compounds are determined).In addition, Liu et al (2019) [22] reported the concentration of rutin in common buckwheat (62.19 mg/kg d.w.) that was in the same order as that obtained in de-hulled grain meal (87.33 mg/kg d.w.). According to the results obtained in these previous works, it has shown that rutin in the free form is concentrated in the outer layers, which is in concordance with our results.…”
Section: Quantification Of Free and Bound Phenolic Compounds In Buckwmentioning
confidence: 99%